Nanocrystallization of α-CsPbI3 perovskite nanocrystals in GeS2-Sb2S3 based chalcogenide glass. Issue 12 (September 2020) - Weng, Kaibo; Long, Nengbing; Guo, Yueqi; Jiao, Qing; Dai, Shixun; Lin, Changgui
Abstract: Black α-phase CsPbI3 of cubic perovskite structure receives intense attentions recently for its unique combination of high photoluminescence quantum yield, suitable bandgap, and long lifetime. However, α-CsPbI3 presents poor chemical and thermodynamic stability under atmosphere condition. Here, we report a strategy for confining the α-CsPbI3 perovskite into chalcogenide glassy matrix through controllable glass nanocrystallization. In the chalcogenide glass with an elaborately designed composition of 80GeS2 ·16Sb2 S3 ·4CsPbI3, spherical α-CsPbI3 nanocrystals were formed and observed clearly, which present good red photoluminescence centered at 701 nm. With the increasing heat-treated temperature, the size of α-CsPbI3 nanospheres increases, while the crystal quantity decreases. It is found that the nanocrystallization of α-CsPbI3 nanospheres in chalcogenide glass is controlled by Ostwald-ripening process.